(untitled) (Global Journal of Human-Social Science, 2024)
The study considers the stages of culture formation through the comprehension of the term Homo excultus. We define the role and place of Homo excultus in the formation of the value space of culture. An attempt has been made, using the latest research in neuroscience and other related disciplines, to explain more fully the reasons for the emergence of Homo excultus. We propose a new vision on the formation of the value system of culture, which began to be created from the moment of uniting people into small communities. The distinctive features of each culture were laid down in these communities in the process when the image of the surrounding world began to be created in the human psychic field. Culture and its values were formed simultaneously. Cultural codes emerged on the basis of values that had already been formed.